Acute kidney injury and dermonecrosis after Loxosceles reclusa envenomation - A Nag (Indian Journal of Nephrology, 2014)
Spiders of the Loxosceles species can cause dermonecrosis and acute kidney injury (AKI). Hemolysis, rhabdomyolysis and direct toxin-mediated renal damage have been postulated. There are very few reports of Loxoscelism from India. We report a case of AKI, hemolysis and a "gravitational" pattern of ulceration following the bite of the brown recluse spider (Loxosceles spp).